PELATIHAN PEMBUATAN E-LKPD MELALUI LIVEWORSHEETS DAN CANVA DI SMPN 3 MERAUKE - Novike Bela Sumanik; Lamtiar Ferawaty Siregar (LPPM Universitas Bina Bangsa, 2023)
Teachers must have competence in the field of technology. This is due to advances in technological development so that teachers must be innovative and creative so that the learning process is not boring. One way is to optimize the use of e-LKPD learning media through the Canva application and liveworksheets. This service aims to improve teachers' pedagogical competence and digital literacy in creating interactive e-LKPD through the Canva application and liveworksheets. This service partner is SMPN 3 Merauke. Subjects who participated in the training were 17 teachers as participants. The methods in this service are theory, practice and question and answer. In this activity the participants were also given a module as a facility in making e-LKPD independently. The conclusion of this service program is that partner problems are resolved and there is an increase in teacher pedagogic competence and digital literacy in making interactive e-LKPD, this is evident from teachers implementing e-LKPD in learning. Therefore, the output target was achieved which showed an increase in partners' skills in making e-LKPD. Teachers at SMPN 3 Merauke expect another training program to train their skills in developing instructional media